What Can We/Do We Want to Know? Reflections from Researching SGBV in Military Settings. (18th December 2018) - Eriksson Baaz, Maria; Gray, Harriet; Stern, Maria
Abstract: This article explores methodological challenges that arose in two perpetrator-centered research projects on sexual and gender-based violence in two different armed forces contexts: the British Army and the Armed Forces of the Democratic Republic of Congo. We examine how the interplay between research subjects', in this case perpetrators', performances and our own desires and investments as researchers shape the knowledge we produce. Ultimately, we seek to encourage continuing (self)critical discussions on how various discursive framings and ethico-political desires shape the stories we hear as well as those that we tell.